Hyperthyrotrophinaemia during thyroxine replacement therapy. - McClelland, P. (BMJ Group, 1989)
During the follow-up of 224 cases of treated hypothyroidism, 14 clinically euthyroid patients were found to have elevated serum thyrotrophin and normal total thyroxine concentrations. Closer observation of these patients during the following 27 months resulted in the serum thyrotrophin levels returning to normal spontaneously in 8 patients (Group 1) whilst remaining elevated in 6 (Group 2), despite no significant differences in thyroid hormone levels between the two groups. Serum thyrotrophin in Group 2 patients remained high until an additional 50 micrograms/day thyroxine was prescribed although only 2 patients noted any benefit. Non-compliance or inadequate dosage of thyroxine are the probable causes of this sub-clinical hypothyroidism. Thyroid hormone estimations fail to differentiate the two conditions and we recommend a period of closer observation before making any thyroxine dosage adjustments in order to detect non-compliance.